67.6k views
9 votes
Check whether (x-1) is a factor of 2x²-3x+1 or not ................ ​

2 Answers

8 votes

Answer:

(x - 1) is a factor of 2x² - 3x + 1

Explanation:

Method 1

If (x - 1) is a factor of f(x) = 2x² - 3x + 1 then f(1) = 0

Substitute x = 1 into the equations:

f(1) = 2(1)² - 3(1) + 1

= 2 - 3 + 1

= 0

Therefore, (x - 1) is a factor of 2x² - 3x + 1

Method 2

Factor 2x² - 3x + 1

Find 2 two numbers that multiply to 2 and sum to -3: -2 and -1

Rewrite the coefficient of the middle term as the sum of these 2 numbers:

⇒ 2x² - 2x - x + 1

Factorize the first two terms and the last two terms separately:

⇒ 2x(x - 1) - 1(x - 1)

Factor out the common term (x - 1):

⇒ (2x - 1)(x - 1)

Thus proving that (x - 1) is a product of 2x² - 3x + 1

User Jannes Botis
by
4.9k points
12 votes
Answer: Yes

Explanation:
Check whether (x-1) is a factor of 2x²-3x+1 or not ................ ​-example-1
User Yuriy Mayorov
by
5.1k points